Hubungan Pengetahuan dengan Sikap Menangani Disminore pada Siswi SMP Negeri 21 Kota Bengkulu Tahun 2025 - Ria Emalyanda; Mariza Arfianti; Berlian Kando Sianipar (Jurnal Multidisiplin Dehasen (MUDE), 2026)
According to the World Health Organization (WHO) 2020, around 90% of women suffer from dysmenorrhea, with the incidence of dysmenorrhea being quite high at around 10-16%, among which some experience severe dysmenorrhea. The Ministry of Health of the Republic of Indonesia (Kemenkes RI) reported that around 64.25% of adolescent girls experience dysmenorrhea, with 54.89% experiencing primary dysmenorrhea, with a prevalence ranging between 50 and 90 percent among women of reproductive age. The purpose of this study is to determine whether there is a relationship between knowledge and attitudes in managing dysmenorrhea.The method used is an analytical research design with a cross-sectional approach, and data were collected by distributing questionnaires to 119 eighth-grade respondents at SMP Negeri 21 Kota Bengkulu, using a total sampling technique.The results of the univariate analysis show that almost half of the respondents (43.7%) have sufficient knowledge, the majority of respondents (41.2%) have good knowledge, and (15.1%) have poor knowledge. Most respondents (78.2%) have a positive attitude, while some respondents (21.8%) have a negative attitude. The bivariate analysis results indicate a relationship between knowledge and attitudes in managing dysmenorrhea among students of SMP Negeri 21 Kota Bengkulu in 2026, with a p-value of (0.001).The researchers suggest that future researchers investigate other factors that influence attitudes toward managing dysmenorrhea, using a design and sample size that are more diverse.